PENGARUH MEDIA SWORDS DALAM MENINGKATKAN HASIL BELAJAR SISWA SD DENGAN MENGGUNAKAN MODEL PEMBELAJARAN ONCE - Dani Darmawan; Kinda Makdalena Eliasar; Henny Dewi Koeswanti; Adi Winanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to determine the influence of SMORDS media in improving elementary school student learning outcomes using the ONCE learning model. By using a type of classroom action research (PTK) and the methods used in collecting data are observation and interviews. This research was conducted at SD Negeri Salatiga 06 with a sample of two classes, namely classes VI A and VI B. The results of this research can be seen that after providing material treatment using Smart Words (SMORDS) media in Indonesian language learning, students were able to develop critical thinking skills, creativity and improve their learning outcomes as evidenced by the results of evaluation tests carried out which resulted in students getting a score of 81-100 and a percentage of 60%.